Синтез та властивості фоточутливих вуглецьвмісних плівок діоксиду титану - Vityuk, N. V.; Smirnova, N. P.; Busko, T. O.; Kulish, M. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
C-TiO2 films were synthesized by sol-gel method using α-terpiniol as a source of carbon. The anatase phase in the films was determined using XRD and Raman techniques. For C-TiO2 films after treatment at 2000С in the Raman spectra fluctuations are observed in the 1604 cm-1, which indicate the presence of carbon in the films. C-TiO2 films obtained are effective photocatalysts for redox processes. The most active films on irradiation with visible light were those with the C–TiO2 ratio of 2,5 after treatment at 2000С and 5000C.